Pedagogical terms of correction of motive sphere of persons of ripe years with the purchased blindness by facilities of playing activity - Kemkina V.I (Kharkov National Pedagogical University, 2011)
The problem of correction of motive sphere of adults blind facilities of playing activity is considered. The pedagogical terms of correction of motive sphere of adults with the purchased blindness are considered. In experiment took part blind adults at the age 22-35 years. It is set that correction-developing teaching the motive actions of blind adults must be concertedly with the level of their development and the differentiated individual approach is foreseen. It is recommended to be oriented on the level of general development of these people, exposure of their potential and actual motive possibilities. It is well-proven that systematic application of facilities of motive activity is provided by the valuable mastering of vitally important motions, development of motive capabilities and capacity for an orientation in space.